The Interconnection of Islamic Law and Human Rights: A Comparative Analysis of Imam Ghazali and Bertrand Russell - Agus Setiawan, Muhammad; Haseena Armina, Sheema; Hadi Untung, Syamsul (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
The relationship between Islamic law and human rights is a complex and controversial topic. Imam Ghazali, a prominent Muslim scholar, put forward the concept of Hifdz Nafs, which emphasizes the importance of protecting the human soul (Hifdz Nafs). Meanwhile, Bertrand Russell, a Western philosopher, espoused a humanistic philosophy that prioritizes the dignity and rights of individuals. This research aims to analyze and compare Imam Ghazali's views on Hifdz Nafs with Bertrand Russell's humanistic philosophy. By comparing these two perspectives, this research hopes to find fundamental similarities and differences that can enrich discussions on Islamic law and human rights. This research uses a qualitative method with a comparative approach. Data was collected through a literature study of the works of Imam Ghazali and Bertrand Russell, as well as relevant academic research. The analysis was conducted by comparing the main concepts of the two figures, as well as reviewing their historical and philosophical contexts. The results show that despite significant differences in their theological and philosophical foundations, both Imam Ghazali and Bertrand Russell recognize the importance of human protection and dignity. Imam Ghazali emphasizes the importance of the safety of the soul as part of maqashid al-shariah, while Russell emphasizes individual rights as the core of humanistic philosophy. This research provides new insights into how Islamic law and Western philosophy can dialogue and interconnect in an effort to strengthen the protection of human rights. It is hoped that the results of this research will provide a basis for further discussion and the development of more inclusive policies.